ANALISIS FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KEJADIAN STUNTING PADA BALITA - Supriyatun Supriyatun (JKM (Jurnal Kebidanan Malahayati), 2021)
Background : Indonesia is still facing nutritional problems that have a serious impact on the Quality of Human Resources (HR). One of the nutritional problems that has become a major concern at this time is the high number of stunting children. Indonesia is a country with a high prevalence of malnutrition in toddlers. In 2019, the prevalence of stunting in toddlers in Indonesia was 27.7 percent, in West Java in 2018 there was 19.4 percent, in the city of Banjar in 2020 there were 8.26% under five with stunting and in the working area of the Purwaharja 2 Health Center itself in 2020 there are 25 cases. The causes of stunting are very complex, including a history of LBW, history of exclusive breastfeeding, mother's education, family socio economic status and birth spacing.Objective: to analyze the risk factors associated with the incidence of stunting in toddlers in the Work Area of the Purwaharja 2 Public Health Center, Banjar City in 2020.Methods:. The type of research used is correlational research using Case Control design. The research analysis used Chi-square and multivariable analysis to see which factor was the most dominant using multiple logistic regression analysis. The number of research subjects as many as 50 people with details of the case group of 25 respondents and the control group of 25 respondents. The sampling technique used is total sampling. The measuring instrument used is a checklist.Results: univariate analysis found under five with a history of not LBW 43 respondents (86%) toddlers with a history of LBW 7 respondents (14%) under five with a history of exclusive breastfeeding 40 respondents (80%) under five without exclusive breastfeeding 10 respondents (20%), maternal education middle school 34 respondents (68%) basic education 11 respondents (22%) higher education 5 respondents (10%), socio economic status in the non-poor family category 37 respondents (74%) in the poor family category as many as 13 respondents (26%), birth spacing category more than equal to 2 years 43 respondents (86%) less than 2 years category as many as 14 respondents (14%). The results of the bivariate analysis were only the history of LBW that had a significant relationship with the incidence of stunting with a P-value 0.010.Conclusion: The risk factor associated with the incidence of stunting in the work area of the Purwaharja II Public Health Center in Banjar Municipality is a history of low birth weight.Suggestion: improve counseling for all mothers who have under five, especially those with under five with a history of LBW about the incidence of stunting, whether it's recognizing what the characteristics are, and how to prevent it, it is hoped that early detection and early management of under five can be made who experienced stunting Keywords: stunting, risk factors, toddlers ABSTRAK Latar Belakang : Indonesia masih menghadapi permasalahan gizi yang berdampak serius terhadap Kualitas Sumber Daya Manusia (SDM). Salah satu masalah gizi yang menjadi perhatian utama saat ini adalah masih tingginya anak balita pendek (Stunting). Indonesia merupakan negara dengan prevalensi gizi kurang pada balita cukup tinggi. Pada tahun 2019, prevalensi balita stunting Indonesia sebesar 27,7 persen, di jawa barat di tahun 2018 terdapat 19,4 persen, di kota Banjar pada tahun 2020 tercatat 8,26% balita dengan stunting dan  di wilayah kerja Puskesmas Purwaharja 2 sendiri pada tahun 2020 terdapat 25 kasus. Penyebab stunting sangat kompleks diantaranya adalah riwayat BBLR, Riwayat pemberian ASI ekslusif, Pendidikan ibu, status sosial ekonomi keluarga dan jarak kelahiran.Tujuan : menganalisis faktor resiko yang berhubungan dengan kejadian stunting pada balita di Wilayah Kerja Puskesmas Purwaharja 2 Kota Banjar tahun 2020.Metode : Jenis penelitian yang digunakan adalah penelitian korelasional dengan menggunakan rancangan Kasus Kontrol. Analisis penelitian menggunakan Chi-square. Jumlah subjek penelitian sebanyak 50 orang dengan rincian kelompok kasus 25 responden dan kelompok kontrol sebanyak 25 responden. Tekhnik sampling yang digunakan adalah total sampling. Alat ukur yang digunakan adalah lembar ceklis. Hasil : analisis univariat didapatkan balita dengan Riwayat tidak BBLR 43 responden (86 %) balita dengan Riwayat BBLR 7 responden (14 %) balita dengan Riwayat ASI ekslusif 40 responden (80 %) balita tidak ASI ekslusif 10 responden (20 %), pendidikan ibu menengah 34 responden (68 %) pendidikan dasar 11 responden (22 %) pendidikan tinggi 5 responden (10 %),  status sosial ekonomi kategori non gakin 37 responden (74 %) kategori gakin yaitu sebanyak 13 responden (26 %),   jarak kelahiran kategori lebih dari sama dengan 2 tahun 43 responden (86 %) kategori kurang dari 2 tahun yaitu sebanyak 14 responden (14 %). Hasil analisis bivariat hanya faktor riwayat BBLR yang mempunyai hubungan yang bermakna dengan kejadian Stunting dengan P-value 0,010.Kesimpulan : Faktor risiko yang berhubungan dengan kejadian stunting di wilayah kerja Puskesmas Purwaharja II Kota Banjar adalah riwayat BBLRSaran :  meningkatkan penyuluhan bagi semua ibu yang memiliki balita khususnya yang memiliki balita dengan riwayat BBLR tentang kejadian stunting baik itu mengenali apa saja ciri-cirinya, dan bagaimana upaya pencegahannya, hal ini diharapkan agar dapat dilakukan deteksi lebih dini dan   melakukan penatalaksanaan lebih awal terhadap balita yang mengalami kejadian stunting Kata kunci : stunting, faktor risiko, balita